Significance of Maternal and Cord Blood Nucleated Red Blood Cell Count in Pregnancies Complicated by Preeclampsia. (6th March 2014) - Hebbar, Shripad; Misha, Mehak; Rai, Lavanya
Abstract : Objectives. To evaluate the effect of preeclampsia on the cord blood and maternal NRBC count and to correlate NRBC count and neonatal outcome in preeclampsia and control groups. Study Design. This is a prospective case control observational study. Patients and Methods. Maternal and cord blood NRBC counts were studied in 50 preeclamptic women and 50 healthy pregnant women. Using automated cell counter total leucocyte count was obtained and peripheral smear was prepared to obtain NRBC count. Corrected WBC count and NRBC count/100 leucocytes in maternal venous blood and in cord blood were compared between the 2 groups. Results. No significant differences were found in corrected WBC count in maternal and cord blood in cases and controls. Significant differences were found in mean cord blood NRBC count in preeclampsia and control groups (40.0 ± 85.1 and5.9 ± 6.3, P = 0.006 ). The mean maternal NRBC count in two groups was2.4 ± 9.0 and0.8 ± 1.5, respectively (P = 0.214 ). Cord blood NRBC count cut off value ≤13 could rule out adverse neonatal outcome with a sensitivity of 63% and specificity of 89%. Conclusion. Cord blood NRBC are significantly raised in preeclampsia. Neonates with elevated cord blood NRBC counts are more likely to have IUGR, low birth weight, neonatal ICU admission, respiratory distress syndrome, and assisted ventilation. Below the count of 13/100 leucocytes, adverse neonatal outcome is quite less likely.